Límites al contenido de la negociación colectiva impuestos por el Estado a sus trabajadores - Neves Mujica, Javier (2014)
Collective bargaining is one of the most important manifestations of the right   to freedom of association, because it serves as the mean through which unions can, progressively, improve labor conditions. It is because of its importance that the contentof this right cannot find itself limited in the possibility for employees  to negotiate their own remuneration, which is what is happening with public employees in our country.In this article, the author makes an analysis of the content of the right of collective bargaining and its limitations imposed by our regulation, from the perspective  of various national and international bodies. Those limitations would be unconstitutional, for they are restraining part of the essential content of the right of collective bargaining, existing, moreover, more suitable measures to achieve the balance between this right and public budget needs.